Evaluasi Model CIPP Implementasi Kebijakan Transit Oriented Development di Kawasan Blok M – Sisingamangaraja - Manurung, Claudie Kezia; Yusuf, Maulana (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
Rapid urban sprawl in Jakarta has restricted access to public spaces and intensified reliance on private vehicles, prompting the city government to adopt a Transit Oriented Development (TOD) policy as a strategic response to promote integrated and sustainable urban mobility. This study specifically investigates the effectiveness of TOD implementation in the Blok M – Sisingamangaraja area, focusing on how well it enhances multimodal connectivity, optimizes land use integration, and supports inclusive access to urban infrastructure. This study aims to evaluate the implementation of the TOD policy in this area using a descriptive qualitative approach. Data were collected through field observations, interviews with relevant stakeholders, and document analysis. The data were analyzed using the Miles and Huberman model, and the evaluation framework applied was the CIPP model (Context, Input, Process, Product) developed by Stufflebeam. The findings indicate that the implementation of TOD in the Blok M – Sisingamangaraja area has not been fully effective. Key issues include non-inclusive pedestrian access around Blok M Terminal and Blok M Square, the lack of direct connectivity between Blok M Terminal and the MRT Station, the persistence of on-street parking that contradicts TOD principles, and the absence of affordable housing for lower-middle-income groups. Based on these findings, the study recommends that PT MRT Jakarta prioritizes the development of affordable housing and enhance inclusive public facilities such as pelican crossings, guiding blocks, pedestrian-friendly access, dedicated and protected bicycle lanes, and integrated bike-sharing systems to support safety, accessibility, and long-term sustainability in the TOD area.